Effect of diaphragm fatigue on subsequent exercise tolerance in healthy men and women - Welch, Joseph F.; Archiza, Bruno; Guenette, Jordan A.; West, Christopher R.; Sheel, A. William (Journal of applied physiology (1985), 2018)
Women are more resistant to diaphragmatic fatigue (DF) and experience an attenuated inspiratory muscle metaboreflex relative to men. The effects of such sex-based differences on whole body exercise tolerance are yet to be examined. It was hypothesized that DF induced prior to exercise would cause less of a reduction in subsequent exercise time in women compared to men. Healthy men ( n = 9, age = 24 ± 3 yr) and women ( n = 9, age = 24 ± 3 yr) completed a maximal incremental cycle test on day 1. On day 2, subjects performed isocapnic inspiratory pressure-threshold loading (PTL) to task failure followed by a constant load submaximal time-to-exhaustion (TTE) exercise test at 85% of the predetermined peak work rate. On day 3, subjects performed the same exercise test without prior induced DF. Days 2 and 3 were randomized and counterbalanced. Magnetic stimulation of the phrenic nerve roots was used to nonvolitionally assess DF by measurement of transdiaphragmatic twitch pressure ( P di,tw ). A similar degree of DF was produced in both sexes following PTL [ P di,tw (% change from baseline): M = −24.6 ± 7.8%, W = −23.1 ± 5.4%; P = 0.54)]. There was a significant reduction in TTE with prior induced DF compared with the control condition in both men (10.9 ± 3.5 min vs. 13.0 ± 3.2 min, P = 0.05) and women (10.1 ± 2.4 min vs. 12.2 ± 3.3 min, P = 0.03) that did not differ in magnitude between the sexes (M = −15.8 ± 19.5%, W = −14.5 ± 19.2%, P = 0.89). In conclusion, DF negatively and equally impairs exercise tolerance independent of sex. NEW & NOTEWORTHY Women are more resistant to diaphragmatic fatigue (DF) relative to men. The effect of DF on exercise tolerance is currently being debated. Our findings show that DF negatively and equally affects exercise tolerance in healthy men and women. Mechanisms beyond the inspiratory muscle metaboreflex (e.g., dyspnea, central fatigue, breathing pattern) may explain the absence of a sex-based difference.